A new silver-zinc battery configuration the use of a rotating vertical zinc electrode in the charging cycle - Jose, Wilfredo I. (Philippine Engineering Journal)
A new design of a silver zinc cell is presented. The system consists of a circular zinc electrode disk (negative electrode) which is rotated on the perpendicular axis passing thru its center and two circular disks with porous silver oxide coating (positive electrode) sandwiching the negative electrode. The electrolyte is 40 percent potassium hydroxide solution. The cell is charged with both the zinc electrode being rotated in a set of runs and stationary in another set. The rotating electrode has a more uniform plating of zinc while the stationary electrode has dendritic and mossy growth and unevenly plated zinc. The performance of the cells at the two different conditions are nearly identical. Problems on the proper current distribution as well as electrical contact in the negative electrode were encountered. The design can help increase the number of charge discharge cycles of the cell. However, the energy density is lower due to the space requirements of the rotating disk and accessories.